2002
DOI: 10.1161/hy1201.096816
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 2 Receptor Counter-Regulates Type 1 Receptor in Catecholamine Synthesis in Cultured Porcine Adrenal Medullary Chromaffin Cells

Abstract: Abstract-We previously showed that CGP 42112 (an angiotensin type 2 [AT 2 ] agonist) markedly reduces catecholamine biosynthesis by decreasing cGMP production mediated by AT 2 , a subtype of Ang II receptor that is dominantly expressed in cultured porcine chromaffin cells. To elucidate the relationship of the 2 types of Ang II receptors, angiotensin type 1 (AT 1 ) and AT 2 , in the synthesis of catecholamine in adrenal medullary cells, we have examined the effect of Ang II plus CV-11974 (an AT 1 antagonist tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
1
17
1
Order By: Relevance
“…22,23 In addition, a counter-regulatory role in catecholamines synthesis by adrenal medullary chromaffin cells has been reported. 24 Supporting this hypothesis, we suggest that AT 2 sites counter-regulate the facilitatory actions of Ang II on NE release at its type 1 receptors because the AT 2 sites are involved in the decreased NE release caused by Ang-(1-7) (present results).…”
Section: Discussionsupporting
confidence: 78%
“…22,23 In addition, a counter-regulatory role in catecholamines synthesis by adrenal medullary chromaffin cells has been reported. 24 Supporting this hypothesis, we suggest that AT 2 sites counter-regulate the facilitatory actions of Ang II on NE release at its type 1 receptors because the AT 2 sites are involved in the decreased NE release caused by Ang-(1-7) (present results).…”
Section: Discussionsupporting
confidence: 78%
“…In spite of this, the selective blockade of AT 1 receptors is sufficient to prevent Ang II-induced catecholamine release in isolated rat adrenal glands (Wong et al, 1990), and longterm inhibition of this receptor subtype decreases both adrenomedullary TH mRNA and norepinephrine content (Armando et al, 2001(Armando et al, , 2004Jezova et al, 2003). In contrast, the role of the dominant AT 2 receptor subtype in the regulation of adrenomedullary catecholamine biosynthesis is not clear, since both activation (Takekoshi et al, 2000(Takekoshi et al, , 2002 and inhibition (Jezova et al, 2003) of this receptor subtype were found to reduce TH expression and catecholamine biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation might be that the effects of exercise-induced AT 1 downregulation are masked by other beneficial effects of CR. For example, elevated levels of AT 2 receptors caused by CR may have an inhibitory effect on TH and DβH expression by opposing AT 1 signaling (Takekoshi et al, 2000(Takekoshi et al, , 2002, therefore downregulation of AT 1 receptors due to exercise does not have further effects on baseline TH and DβH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Since therapies targeting both AT1 and AT2 receptors and angiotensin converting enzyme have proven successful in regulating the catecholaminergic system in different cardiovascular pathologies, such as hypertension and heart failure (Kawai et al, 2000;Takekoshi et al, 2002), it is suggested that these therapies may be used to target downstream signaling pathways stimulated in common by either MK or PTN in conditions in which expressions of either Mk and Ptn (or both) are elevated, such as systemic sclerosis with diffuse scleroderma (Whitfield et al, 2003). Other functions of Mk expression may be regulated through the catecholamine and/or renin-angiotensin pathways as well; Mk −/− mice have reduced neointima formation in restenosis injury models that is reversible by systemic administration of MK (Horiba et al, 2000) and antisense Mk oligodeoxyribonucleotides suppress neointima formation after injury (Hayashi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%